2001
DOI: 10.1074/jbc.c100416200
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of RYR1 and L-type Calcium Channels via Calmodulin Binding Domains

Abstract: In skeletal muscle the L-type Ca 2؉ channel directly controls the opening of the sarcoplasmic reticulum Ca 2؉ release channel (RYR1), and RYR1, in turn, prevents L-type Ca 2؉ channel inactivation. We demonstrate that the two proteins interact using calmodulin binding regions of both proteins. A recombinant protein representing amino acids 1393-1527 (D1393-1527) of the carboxyl-terminal tail of the skeletal muscle L-type voltage-dependent calcium channel binds Ca 2؉ , Ca 2؉ calmodulin, and apocalmodulin. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 26 publications
2
45
0
Order By: Relevance
“…We previously have shown that a carboxyterminal tail fragment of the skeletal L-type channel (Ca v 1.1) a 1 -subunit, which contains both Ca 21 and CaM binding sites, binds to RyR1. This interaction is blocked by Ca 21 CaM (26). We have also shown that a peptide representing the CaM binding site on RyR1 (amino acids 3614-3643) binds to both the Ca v 1.1 and an expressed fragment of the carboxyterminal tail of its a 1 -subunit (amino acids 1393-1527) (26).…”
Section: Introductionmentioning
confidence: 80%
See 4 more Smart Citations
“…We previously have shown that a carboxyterminal tail fragment of the skeletal L-type channel (Ca v 1.1) a 1 -subunit, which contains both Ca 21 and CaM binding sites, binds to RyR1. This interaction is blocked by Ca 21 CaM (26). We have also shown that a peptide representing the CaM binding site on RyR1 (amino acids 3614-3643) binds to both the Ca v 1.1 and an expressed fragment of the carboxyterminal tail of its a 1 -subunit (amino acids 1393-1527) (26).…”
Section: Introductionmentioning
confidence: 80%
“…This interaction is blocked by Ca 21 CaM (26). We have also shown that a peptide representing the CaM binding site on RyR1 (amino acids 3614-3643) binds to both the Ca v 1.1 and an expressed fragment of the carboxyterminal tail of its a 1 -subunit (amino acids 1393-1527) (26).…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations